Análise da validade nas ações comunicativas: reconstrução do entendimento na pragmática formal. - Alves, Pedro Spíndola Bezerra (2024)
The present thesis has the theme of formal pragmatics of Jürgen Habermas, starting from the research problem of whether it is possible – to what extent and in what ways – to analyse the validity present in communicative actions, in order to reconstruct the understanding that embodied it in a given concrete situation. To do so, it presents an in-depth explanation of formal pragmatics and the concept of communicative action in Habermasian philosophy, with the aim of apprehending the meaning and limits of the concept of validity in his philosophy. The hypothesis of the thesis, deployed especially in its final chapter, is that it is indeed possible, with Habermas, to reconstruct understanding and its validity claims in a given communicative action, but with a double restriction or conditioning. The first concerns the framing of what can enter as an effectively formal analysis, including the pragmatic Habermasian proposal, which refers to the issue of the extent. And the second, regarding what depends on the construct to be created from the actual life’s world from which the language action that one wants to analyze is born; this is the question of mode. Testing this hypothesis requires crossing, with Habermas, the understanding of the reconstruction of his formal pragmatics, from the linguistic turn, and the theory of communicative action, especially regarding the concepts of communicative rationality and the lived world, which is carried out in the chapters first and second. The final chapter apprehends the extract related to everything that has been understood about validity and concludes by the need for specific communicative production – endogenous to the life’s world considered – of mechanisms for redeeming validity to enable an analysis that may intend to offer new interpretations to the life’s world, beyond mere abstraction. Finally, this thesis ends with an excursus discussing what it proposes to contribute to the Language Sciences, succinctly launching itself into examples of analysis traits to demonstrate the pertinence of what was discussed, although an analysis in fact requires, as presupposed by the thesis itself, a deepening in new research to (re)construct the specific validity claims mechanism of the life’s world analyzed. The method used was the reconstructive one, proposed by Habermas, inscribed in his formal pragmatics, and as for the technical procedures, the research is bibliographical, with consultations to books and articles published in specialized journals.